2016
DOI: 10.5539/mas.v10n8p264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Performance in the Disc Filter with Sand Filters of Filtration Equipment in Micro Irrigation Systems

Abstract: At the present time, the need to evacuate organic and green growth of algae contaminants in micro irrigation system is expanding increasingly. The worldwide populace is expanding and as a result of this, the world may encounter extraordinary fresh water shortage. Our water assets are constrained and, subsequently, water treatment and reusing strategies are the main choices for getting crisp and fresh water in the coming decades. This study examines the rate of the impact of green growth of algae existing in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…As such a sample of water emitting from the central control the amount of suspended material was calculated and filtration percentage determined. Ghaffari and Soltani [16].…”
Section: Flow Ratementioning
confidence: 99%
“…As such a sample of water emitting from the central control the amount of suspended material was calculated and filtration percentage determined. Ghaffari and Soltani [16].…”
Section: Flow Ratementioning
confidence: 99%
“…The adoption of an integrated agriculture aquaculture system, in which agricultural and aquaculture products are managed in an integrated way, contributes to improved production sustainability, resource productivity, and environmental sustainability (WWAP, 2017). The most effective system for the reuse of e uent is drip irrigation in which emitter clogging is a challenge that depends on emitter type (Maroufpoor et al, 2020), geometric structure of the emitter (Lequette et al, 2020b;Aminpour et al, 2021), water quality (Capra and Scicolone 2001) and ltration e ciency (Tripathi et al, 2014;Ghaffari and Soltani, 2016). So far, various solutions have been proposed to solve this problem in drip irrigation systems such as ushing and lateral drainage, chlorination, and pressure ushing of drippers (Puig-Bargués et al, 2010; Song et al, 2017;Lequette et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Disc lters perform better in the removal of the sand particles than clay particles (Khan et al, 2017). Also, for ltration of suspended solids up to a concentration of 50 mg l − 1 , conventional disc lters, and for concentrations of 50-100 mg l − 1 , automatic disc lters are effective (Ghaffari and Soltani 2016). An increase in the inlet pressure leads to an enhanced ltration e ciency (Kumar et al, 2017;Duran-Ros et al, 2009a, but it might lead to no effect in the ltration e ciency of disc lters, screen lters, or a combination of both (Kumar et al, 2017;Duran-Ros et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the removal efficiency decreased with increasing the grain size of sand filter, as it was previously observed by Duran-Ros et al (2009). Ghaffari and Soltani (2016) showed that disc filters had a good efficiency in removing suspended and organic solid concentrations from 50 to 100 mg/l, but beyond 100 mg/l their performance was significantly reduced. Therefore, the use of sand filters is recommended before the disc filter.…”
Section: Introductionmentioning
confidence: 99%